Stochastic Resonance and Dynamic First-Order Pseudo-Phase Transitions in the Irreversible Growth of Thin Films under Spatially Periodic Magnetic Fields - Loscar, Ernesto Selim (2013)
We study the irreversible growth of magnetic thin films under the influence of spatially periodic fields by means of extensive Monte Carlo simulations. We find first-order pseudo-phase transitions that separate a dynamically disordered phase from a dynamically ordered phase. By analogy with time-dependent oscillating fields applied to Ising-type models, we qualitatively associate this dynamic transition with the localization/delocalization transition of “spatial hysteresis” loops. Depending on the relative width of the magnetic film, L, compared to the wavelength of the external field, λ, different transition regimes are observed. For small systems (L < λ), the transition is associated with the Standard Stochastic Resonance regime, while, for large systems (L > λ), the transition is driven by Anomalous Stochastic Resonance. The origin of the latter is identified as due to the emergence of an additional relevant lengthscale, namely the roughness of the spin domain switching interface. The distinction between different stochastic resonance regimes is discussed at length, both qualitatively by means of snapshot configurations, as well as quantitatively via residence-length and order-parameter probability distributions